Pengaruh Konten Populer Isu Boikot Pada Produk Terafiliasi Israel Di Media Sosial Tiktok Terhadap Keputusan Boikot Mahasiswa Jurnalistik - Syamsidar; Nurhikmawati (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2025)
This study aims to determine the influence of popular content related to the issue of boycotting Israeli-affiliated products on TikTok social media on the decision to boycott by active students majoring in Journalism, Faculty of Da'wah and Communication, UIN Alauddin Makassar. This study uses a descriptive quantitative approach with a survey method using an online questionnaire. The data analysis technique uses simple linear regression through SPSS software. The results of the study show that popular content on the boycott issue on TikTok has a significant influence on students' decision to boycott, with a coefficient of determination of 23.2%. This means that 76.8% of the boycott decision is influenced by other factors not examined in this study. This study emphasizes the importance of the role of social media in shaping opinions and social actions on global issues.